2021
DOI: 10.1111/php.13487
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Oxygen Generation, Quenching and Reactivity with Metal Thiolates

Abstract: Metal thiolate complexes can act as photosensitizers for the generation of singlet oxygen, quenchers of singlet oxygen, and they may undergo chemical reactions with singlet oxygen leading to oxidized thiolate ligands. This review covers all of the chemical reactions of thiolate ligands with singlet oxygen (through early 2021). Since some of these reactions are selfsensitized photooxidations, singlet oxygen generation by metal complexes is also discussed. Mechanistic features such as the effects of protic vs. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 123 publications
0
8
0
Order By: Relevance
“…It has also been reported that cyclometallated monocationic complexes of iridium(III) and platinum(II) are effective singlet oxygen photosensitizers. 67,68 Cyclometallated platinum(II) complexes, 69,70 were found to be efficient singlet oxygen photosensitizers. The photophysical properties and efficiency of singlet oxygen production photosensitized by thirty eight Re(I) complexes have been recently collected and singlet oxygen quantum yields were reported with the minimum value of 0.20 and highest value approaching unity.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that cyclometallated monocationic complexes of iridium(III) and platinum(II) are effective singlet oxygen photosensitizers. 67,68 Cyclometallated platinum(II) complexes, 69,70 were found to be efficient singlet oxygen photosensitizers. The photophysical properties and efficiency of singlet oxygen production photosensitized by thirty eight Re(I) complexes have been recently collected and singlet oxygen quantum yields were reported with the minimum value of 0.20 and highest value approaching unity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on singlet oxygen photosensitization by coordination compounds are very limited in comparison with those reported for aromatic compounds. ,,, The majority of these studies have been concerned on the study of singlet oxygen generation photosensitized by ruthenium­(II) polypyridyl complexes in aqueous and nonaqueous media. Photosensitization of singlet oxygen by metal complexes other than Ru­(II) has also been reported using, for example, complexes of Pd­(II) and Pt­(II), , Os­(II) with terpyridyl ligands, Au­(I), Ir­(III), ,, and Re­(I) …”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, peroxy intermediates arise in various photooxidation and regular oxidation reactions. These intermediates include R 2 C + OO − carbonyl oxide, RN + OO − nitrosooxide, R 2 NN + (=O)OO − nitrooxide, R 2 Si + OO − silanone oxide, R 2 S + OO − persulfoxide and R 2 Te + OO − pertelluroxide (14–25). Peroxy intermediates have been implicated in lowering the energy barrier for cis ‐ trans isomerization of alkene and polyene CC bonds (1).…”
Section: Introductionmentioning
confidence: 99%